Latitudinal patterns of bird richness, diversity and abundance in Polylepis australis mountain forest of Argentina - Bellis, Laura Marisa (2009)
Many South American hotspots of bird endemism are found in Polylepis dominated forests. Although the avifauna of Polylepis forests has been relatively well studied in the tropical Andes, little is known in Argentina. In this study, we characterize the Argentine avifauna of Polylepis australis forests along their entire latitudinal gradient of distribution and provide a first systematic bird list and their conservation status. Fieldwork was carried out from 1,500 to 2,800 m a.s.l. in three study sites: North (Jujuy province), Centre (Tucumn province) and South (Crdoba province); we surveyed 30 point counts per site. We recorded 543 individuals belonging to 50 bird species; two subspecies are endemic to the South site and four species are typical Polylepis forest birds of the North and Centre sites. We identified four species of conservation concern; one globally threatened and three declining at regional level. Bird richness and abundance decreased with latitude; and equitability showed an inverse pattern. Sorenson's similarity index ranged from 12% to 40% showing a large latitudinal turnover in avian communities. Disturbance-sensitive species were the most diverse group in the North site. Variations in species richness, evenness and guild composition may be a response to latitude, but also to differences in habitat complexity and food availability, which appear to be a consequence of forest degradation at the South site. We recommend: (1) the enlargement of Calilegua National Park to include the Polylepis australis belt to assure the conservation of many disturbance-sensitive species which could decline or disappear in degraded areas; (2) management of Quebrada del Condorito National Park to increase the forest structure complexity and therefore provide habitat for disturbance-sensitive species. © BirdLife International 2009.